Why human rights still matter in contemporary global affairs - Monshipouri, Mahmood 1952- (Routledge studies in human rights, 2020)
This book elucidates why human rights still matter in contemporary global affairs, and what can lead to better protection of international human rights in a post-liberal order. It blends theoretical, empirical, and normative perspectives, while providing much-needed analysis in light of the perils of populism, authoritarianism, and toxic nationalism as well as the hopes with which people around the world view human rights in the new millennium. Systematically combining theoretical perspectives from across the disciplines with numerous case studies, it demonstrates not only the complexities of the domestic conditions involved, but also the ways in which human dignity can be preserved and promoted during periods of rapid change and uncertainty. Finally, the book addresses the question of how to protect human rights in such a world in which the active promotion of democratic values and enforcement of human rights may not be necessarily aligned with evolving economic and geopolitical interests of many great and diverse powers on the global scene. As such, it is a timely intervention for human rights as a concept as it has been attacked and eroded by the instability in our world today. This book will be of key interest to scholars and students of human rights in politics, law, philosophy, sociology, and history and to humanitarian bodies, practitioners and policy makers"--